The Trend of Critical Thinking Studies in Biology Education through Online Learning: A Systematic Review - Nuri, Ayu Rahma Ulfa; Sajidan, Sajidan; Ramli, Murni (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
Biology teachers and students in society 5.0 are expected to show critical thinking skills (CTS) in solving problems or making decisions. Thus, it is important to know how the CTS are nurtured through online learning. The trend of studies on these issues needs to be explored. This research aims to map the trend of studies on nurturing the CTS through online learning by reviewing some articles published within 2018-2020, considering 1) the online learning, 3) topics in biology, 4) teaching methods, and 5) instruments of CTS. Following the systematic review of the PRISMA Method, articles were screened from Google Scholar. The keywords were "critical thinking", "biology education", "online learning", and "Indonesia", which resulted in 23 articles to be further reviewed. The findings show that CTS's research trends using online learning have increased due to the COVID-19 pandemic that requires students and teachers to distance studies. The most used online learning was digital learning. The researchers used various topics in biology to measure students' CTS using online learning but mainly genetics and cell biology. The most widely used teaching method is blended learning and online discussion which various learning models can combine learning methods or learning media. The test is mainly used as an instrument to measure CTS with various indicators presented by experts. Research on CTS using online learning needs to be further explored to increase the quality of the study